Akamu paste from white and yellow maize spiced with uda (Xylopia aethiopica) and uziza (Piper guineenses) intended for postpartum Nigerian mothers: micronutrient and anti-nutrient diversity - Innocent Okwunodulu; Gladys Chima; Anslem Onwuzurike; Felicia Okwunodulu (Cogent Food & Agriculture)
Uda and uziza hot pepper soup are taken postpartum instead of antibiotics till date, hence this study on their micronutrients and safety implications. Cleaned white and yellow maize were separately co-fermented (72 h) with both spices, drained, washed, milled, sieved and dewatered to obtain the semi-solid spiced akamu pastes. Same process was repeated but the spices were added raw at the point of milling. Akamu paste from steeped and un-spiced maize samples served as controls. Micronutrients and anti-nutrients content of the akamu pastes were evaluated. Results showed that vitamins (mg/100g) B1 ranged from 0.315 to 0.460, B2 0.125–0.160 and methionine 42.240–52.810. Potassium ranged from 170.72 to 202.12, magnesium 63.14–79.43 and iron 3.12–5.74 mg/100g. Phytate ranged from 7.200 to 9.660, tannin 5.595–6.660 and trypsin inhibitor 1.120–1.625 mg/100g. Maize type, spice type and spicing technique influenced the micronutrients, anti-nutrients and methionine content of the spiced akamu pastes. All the minerals had better bioavailability with negative significant (p < .01) correlation with the anti-nutrients except iron.